La Unión Aduanera Centroamericana: desafíos para avanzar hacia la integración económica - Ocampo Sánchez, Fernando (2016)
In recent years Central America has consolidated its process of economic ntegration through a customs union, the implementation of free trade between its members and the establishment of a common external tariff of morethan 95 % of the tariff lines. These elements have promoted a steady growth of trade of goods and services, not just among the region, but also in external markets. Despite these advances, however, the region still faces major challenges to deepen economic integration, such as: adoption of trade facilitation measures, consolidation of free trade and movement of goods within the customs territory, completion of the common external tariff, designing a Central American joint trade policy, and defining a common tariff and tax collection mechanism, as well as strengthening the institutional and intraregional coordination mechanisms.